Transformation of Elementary School Students' Mathematics Learning Outcomes using the GASING Method in a Critical Pedagogical Approach - Yogina Pratiwi; Yusuf Tri Herlambang; Yeni Yuniarti; Abu Bakar (Journal of Educational Sciences, 2026)
The low mathematics learning outcomes among Indonesian elementary school students remain a significant challenge, particularly due to the dominance of procedural approaches that lack dialogic and reflective dimensions. This condition calls for instructional innovation that not only improves academic achievement but also fosters the transformation of students’ understanding and learning awareness. This study aims to systematically examine the transformation of mathematics learning outcomes through the GASING method within a critical pedagogy framework. The research employed a Systematic Literature Review (SLR) guided by PRISMA 2020, analyzing publications from 2015–2025 retrieved from Google Scholar, Sinta, and Garuda databases. Of the initial 130 identified articles, 13 met the inclusion criteria and were analyzed thematically. The synthesis indicates that the GASING method consistently enhances conceptual understanding, learning mastery, and student participation. However, most studies emphasize short-term quantitative indicators. It is concluded that GASING holds transformative potential when implemented dialogically and reflectively within a critical pedagogy framework to promote sustainable mathematics learning.